URINARY TRACT INFECTION AND PPROM: A CROSS-SECTIONAL STUDY - KHAN , N; IQBAL , A (Biological and Clinical Sciences Research Journal, 2023)
During pregnancy, urinary tract infections (UTIs) are a common issue that can have severe short- and long-term fetal morbidity and death linked to premature membrane rupture and preterm birth. This cross-sectional study aimed to determine the frequency of UTIs in patients with preterm rupture of membranes (PPROM). The study was conducted at the Gynae B unit of Mardan Medical Complex, Dardan, and lasted six months, from January 1, 2023, to August 1, 2023. After obtaining permission, the study included 103 patients with verified PPROM and singleton pregnancy who were hospitalized from the outpatient department or emergency room and had a parity 37 weeks before. Patients with intrauterine mortality, antepartum hemorrhage, or infection that needed immediate treatment were excluded from the study. A midstream urine specimen was obtained from each patient, and information was gathered on the midstream urine specimen outcomes for sensitivity and culture. In our study, the frequency of UTIs in PPROM patients was 20.4% (21 patients). The mean age of patients was 28.922±2.54 years, and the age range was 18 to 35. The mean gestational age was 31.718±1.37 weeks, and the mean parity was 1.534±1.37. Women who were multiparous (18.3%, p=0.00) and older than 30 (17.4%, p=0.00) had higher rates of UTI. Based on our study’s findings, we conclude that there is a strong link between urogenital infections and premature birth, with 20.4% of patients with PPROM having a UTI. As a result, we recommend routine urine testing throughout pregnancy to promptly treat UTIs, mainly asymptomatic UTIs. To reduce the prevalence of PPROM and the resulting morbidity and death in mothers and fetuses, repeated culture monitoring must be conducted.